Lean management methods: Evidence from the manufacturing industry in the Czech Republic - Romana Heinzova; Eva Hoke; Nikola Janova (Problems and Perspectives in Management, 2024)
Lean management is a way to satisfy the increasing customer demands while maintaining production efficiency. This paper aims to map and analyze the level of use of lean management methods in the manufacturing industry in the Czech Republic. It searched for links and dependencies between company size, production type, and lean management methods in operational processes. The data were obtained from a nationwide survey within the manufacturing industry companies and were presented using descriptive statistics. A structured questionnaire was sent to 469 manufacturing companies with a return rate of 18.8%. Nonparametric statistical analysis (Fisher’s exact test) was used to confirm or reject the hypotheses. The research results confirmed the dependence of lean management methods on company size and production type. Lean management methods are used mainly by large enterprises, while micro- and small enterprises rarely employ them. Considering production typology, lean management is applied in serial production, and Single Minute Exchange of Dies (SMED) prevails. The most used techniques in mass production include the method of order in the workplace (5S) and Kaizen. The findings suggest that the future of industrial output should focus on sustainability and rationalization of production resources, which is offered by the synergy of lean management and Industry 5.0. AcknowledgmentThis paper is co-financed by IGA/FLKR/2023/002 Rationalization and Sustainability of Resources in Production-Logistics Processes the Czech Republic and RVO/FLKŘ/2024/01 Logistic Systems Safety.